Development of electronic medical record charting for hospital-based transfusion and apheresis medicine services: Early adoption perspectives - Rebecca Levy; Liron Pantanowitz; Darlene Cloutier; Jean Provencher; Joan McGirr; Jennifer Stebbins; Suzanne Cronin; Josh Wherry; Joseph Fenton; Eileen Donelan; Vandita Johari; Chester Andrzejewski (Elsevier, 2010)
Background: Electronic medical records (EMRs) provide universal access to health care information across multidisciplinary lines. In pathology departments, transfusion and apheresis medicine services (TAMS) involved in direct patient care activities produce data and documentation that typically do not enter the EMR. Taking advantage of our institution's initiative for implementation of a paperless medical record, our TAMS division set out to develop an electronic charting (e-charting) strategy within the EMR. Methods: A focus group of our hospital's transfusion committee consisting of transfusion medicine specialists, pathologists, residents, nurses, hemapheresis specialists, and information technologists was constituted and charged with the project. The group met periodically to implement e-charting TAMS workflow and produced electronic documents within the EMR (Cerner Millenium) for various service line functions. Results: The interdisciplinary working group developed and implemented electronic versions of various paper-based clinical documentation used by these services. All electronic notes collectively gather and reside within a unique Transfusion Medicine Folder tab in the EMR, available to staff with access to patient charts. E-charting eliminated illegible handwritten notes, resulted in more consistent clinical documentation among staff, and provided greater real-time review/access of hemotherapy practices. No major impediments to workflow or inefficiencies have been encountered. However, minor updates and corrections to documents as well as select work re-designs were required for optimal use of e-charting by these services. Conclusion: Documentation of pathology subspecialty activities such as TAMS can be successfully incorporated into the EMR. E-charting by staff enhances communication and helps promote standardized documentation of patient care within and across service lines. Well-constructed electronic documents in the EMR may also enhance data mining, quality improvement, and biovigilance monitoring activities.